The Legal Duty to Consult and Meaningful Consultation: A Spectrum of Industry Approaches to Aboriginal Consultation in the Athabasca Oilsands - Vredenburg, Vanessa (Graduate Studies, 2015)
This thesis presents an in depth analysis of the factors that influence the way in which resource extraction companies in the Athabasca Oilsands region of northern Alberta conduct Aboriginal consultation. The duty to consult arose historically through constitutional foundations, case law, and now is incorporated into regulatory guidance documents. Although the duty to consult has been documented in many different ways throughout history, there is a current shift in consciousness that there is a need to go beyond compliance with legal and regulatory guidance to move towards gaining ‘social compliance’. A review of current literature relating to Aboriginal community and resource extraction company relationships, sustainable development, and gaining a social license show that by going beyond regulatory compliance towards social compliance, a competitive advantage can be gained. Two models were identified to measure the way in which resource extraction companies conducted Aboriginal consultation: the rules model and the relationship model. The rules model is based on the idea that by following regulatory guidelines, project approval can be gained. The relationship model is based on the idea that by establishing long lasting relationships with Aboriginal groups that these companies could not only reach regulatory guidelines but go beyond towards achieving social compliance. Eighteen Aboriginal consultation practitioners who worked on projects in the Athabasca Oilsands region were interviewed to better understand the way in which their companies approached Aboriginal consultation. The data was analyzed based on the rules and relationship model. Through analysis, it was determined that the way in which these resource extraction companies approached consultation was not as black and white as originally thought, but instead could be placed on a spectrum with the rules model being at one end and the relationship model being at the other end. The research determined that in conclusion, the main factor that drove the way in ...